USE OF INNOVATIVE APPROACHES IN HORTICULTURE: A CASE STUDY OF SOPORE - Dr. Zubair Ahmad Bhat (RADJA PUBLIKA, 2023)
Kashmir Valley has got the potential to produce different varieties of fresh apple crop which contributes state gross domestic product and foreign exchange. Apple fruit is one of the important fresh fruits which alone account 44.10 per cent of area and 90 per cent of production in the union territory. Every year millions of apple boxes are being exported to various parts of country and to some neighbouring countries like Bangladesh from various parts of region. To pick, pack and carry the Apples, every year millions of trees were cut down for the manufacturing of wooden crates. With the introduction of cardboard and plastic crates the grower find some relief as it is cheaper and easy to carry from traditional wooden crates. The present paper will try to find out the benefits and usage of cardboard crates in place of traditional wooden crates for marketing of apple.